The hidden grip: A case of secondary hypertension entwined with renal artery stenosis - Rahmawati, Novi; Handari, Saskia Dyah; Hargiyanto, Erlangga Diasmara (Heart Science Journal, 2026)
Background: Renal artery stenosis (RAS) is a vascular disorder characterized by narrowing of the renal artery. It often leads to renovascular hypertension (RVH) and, if untreated, progression to end-stage renal disease. Atherosclerosis and fibromuscular dysplasia (FMD) are the most common etiologies, with clinical manifestations ranging from asymptomatic to resistant hypertension. Diagnosis involves imaging modalities such as Doppler ultrasound (DUS), CT angiography (CTA), and confirmation by digital subtraction angiography (DSA). We report a case to emphasize the diagnostic and therapeutic challenges of RAS in young patients. Case Illustration: A 17-year-old male presented with persistent grade 2 hypertension unresponsive to dual antihypertensive therapy and a history of repeated hospitalizations. Imaging revealed significant stenosis with post-stenotic dilatation in the right renal artery. CTA and DSA confirmed the diagnosis of RVH secondary to RAS, with Fibromuscular Dysplasia (FMD) as the suspected etiology. The patient underwent successful angioplasty and stenting, resulting in improved blood pressure control and reduced medication requirements. Upon follow-up, the patient’s symptoms have resolved, and their blood pressure is under control. RAS remains a challenging and underdiagnosed cause of secondary hypertension, particularly in younger patients. While optimal medical therapy is the first-line approach, it may be insufficient in high-risk individuals. Non-invasive modalities provide valuable initial assessment, but DSA remains the gold standard for diagnosis and intervention. Revascularization, especially via stenting, is recommended in selected cases with significant stenosis, viable renal tissue, and resistant hypertension. Guidelines emphasize tailored therapy and careful post-procedure monitoring to detect restenosis or symptom recurrence. This case underscores the importance of early recognition and individualized intervention to improve outcomes.. Conclusions: RAS should be considered in young patients with grade 2 hypertension. Early diagnosis and appropriate intervention are critical to preventing long-term renal and cardiovascular complications.